From ethnic conflict to stillborn reform : the former Soviet Union and Yugoslavia - Horowitz, Shale Asher (Texas A & M University Press, 2005)
"From Ethnic Conflict to Stillborn Reform is the first complete treatment of the major postcommunist conflicts in both the former Yugoslavia - Bosnia-Herzegovina, Croatia, and Serbia - and the former Soviet Union - Armenia, Azerbaijan, Georgia, Moldova, and Tajikistan. It is also the first work that focuses not on causes but rather on consequences for democratization and market reform, the two most widely studied political outcomes in the developing world." "Building on existing work emphasizing the effects of economic development and political culture, this book offers a new, comprehensive treatment of how war affects political and economic reform."